Amplicon sequencing reveals significantly increased Vibrio abundance and associated gene functions in vibriosis‐infected black tiger shrimp (Penaeus monodon). Issue 5 (18th November 2020) - Foysal, Md Javed; Momtaz, Farhana; Kawser, A.Q.M. Robiul; Ali, Md Hazrat; Raihan, Topu; Siddik, Muhammad A. B.; Rahman, Md Mahbubur; Tay, Alfred
Abstract: Vibriosis caused by luminous Vibrio species is one of the biggest challenges to shrimp industry in Bangladesh. This study aimed to characterize whole microbial communities from Vibrio ‐infected black tiger shrimp ( Penaeus monodon ) using 16S rRNA‐based amplicon sequencing. A total of 36 disease‐free and infected shrimp were collected from six different hatcheries in Bagerhat, Bangladesh. A final pool of 12 samples ( n = 6) was created by homogenization of the hepatopancreas samples from three shrimps collected from each hatchery for the same group. The amplicon sequencing data revealed significant ( p < .05) decrease of alpha diversity measurements and subsequent effects ( p < .05) on the hepatopancreas microbiota in the infected group, compared to control shrimp. Proteobateria and Aeromonas were the most dominant bacteria at phylum and genus level in both groups and identified as core microbiota in the community. Two bacterial groups at phyla level and eight at genus level were found associated with the alteration of hepatopancreas microbial communities and associated gene functions in vibriosis‐infected shrimp, revealed by differential abundance and KEGG pathway analysis. The overwhelming abundance of Citroibacter, Shewanella and Candidatus lineages in vibriosis‐infected shrimp needs further investigations.